The influence of breast plastic surgery on the breastfeeding process: An integrative review (Research, Society and Development, 2023)
This integrative review aims to evaluate the influence of breast plastic surgeries, including breast augmentation, mastopexy and breast reduction, on the practice of breastfeeding. Searches were carried out in scientific databases to identify relevant studies published up to the cutoff date of September 2023. This is an integrative review and its systematization took place through the following steps: a) identification of the guiding question, b) search in digital literature, c) evaluation of findings, d) interpretative analysis of results, e) discussion with summary of knowledge. For the search, combinations of the following indexing terms were used: lactation, breastfeeding, breast plastic surgery, reduction mammoplasty and mastopexy (and their correlates in English). Articles published between 2013 and September 2023 in the PubMed, Scopus, LILACS and SciELO databases were included. Initially, 22 publications were identified during the search. After applying the inclusion and exclusion criteria, a total of 7 works were obtained for inclusion in this study. It is possible to observe that there is a scarcity of works on the topic in world literature. The results of the analysis were categorized and discussed regarding the potential impacts on breastfeeding rates, milk production, mothers' satisfaction and the risk factors associated with which type of breast surgery generates the greatest influence on the breastfeeding process, as well as which The surgical technique performed can have a greater impact on milk production.